Omnimbus Law terhadap Investasi Indonesia - Alexandra, Laveda Epata (Universitas Ekasakti, 2023)
The Omnibus Law aims to improve Indonesia's economic competitiveness by reducing regulations and bureaucracy, cutting red tape, and simplifying business licenses. The Omnibus Law is expected to attract more foreign investment and create jobs. The Omnibus Law in terms of Job Creation will change the business and investment environment in Indonesia. This research uses two ways to conduct legal research, namely normative and sociological juridical or sociological juridical approaches. This research concludes that the Omnibus Law has the potential to attract more foreign investment, create jobs, and improve Indonesia's economic competitiveness during the post-pandemic global crisis. However, the Omnibus Law must be implemented carefully to avoid negative impacts on investment in Indonesia. It is important to note that Indonesia's regulatory problems cannot be solved simply by using the omnibus law method. Instead, the government must create policies to ensure that the regulatory system is improved systematically and continuously. One way to do this is to establish a specialized institution that involves various parties involved in the formation of laws and regulations.Investasi